A usability assessment of e-government websites in Sub-Saharan Africa. (April 2018) - Verkijika, Silas Formunyuy; De Wet, Lizette
Highlights: A usability evaluation was conducted on 279 e-government websites from 31 countries in Sub-Saharan Africa (SSA). The findings showed that most of the websites performed poorly across the six evaluated usability dimensions. A positive association was observed between e-government website usability and the E-Government Development Index (EGDI). Similarly, e-government website usability was also positively associated the E-Participation Index (EPI). Abstract: E-government holds enormous potential for improving the administrative efficiency of public institutions, encouraging democratic governance, and building trust between citizens/private sector and governments. However, most e-government initiatives to date have failed to attain their full potential, because they are increasingly plagued by usability issues. Consequently, there have been increasing calls for evaluating the usability of e-government websites, as they are widely considered to be the primary platform for government interaction with citizens. This study, therefore, seeks to contribute to extant knowledge by evaluating the usability of e-government websites from Sub-Saharan Africa (SSA). This is particularly important as little is known about the usability of e-government websites in the region, and worst still, it is the least advanced region in terms of e-government development. This study evaluated a total of 279 e-government websites from 31 SSA countries. The findings showed that most e-government websites in SSA were characterised by poor usability. The average usability score for the websites was 36.2%, with the most usable website having a score of only 64.8%. The study also showed that the usability of e-government websites was positively associated with the E-Government Development Index (EGDI) and the E-Participation Index (EPI).